2016
DOI: 10.1007/s00392-016-1040-7
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis in patients with atrial fibrillation and a presumed “temporary cause” in a community-based cohort study

Abstract: AF patients with presumed temporary cause of AF had a similar risk of stroke/thromboembolism and a worse prognosis for cardiovascular mortality than other AF patients. Use of oral anticoagulation was associated with a better prognosis in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…This may support the need for stroke prevention in patients with AHREs which is currently under evaluation in randomized control trials; two ongoing trials are exploring this issue [19, 20]. Apart from CIEDs, increasingly sophisticated means of monitoring (e.g., implanted loop recorders) to detect AHREs in various clinical settings and high-risk groups, that would merit consideration of stroke prevention, have been recently investigated [2123]. Of note, a recent consensus document from the European Heart Rhythm Association recommended that patients presenting with subclinical atrial tachyarrhythmias (i.e., AHRE > 5 min) should be considered for oral anticoagulation when ≥ 2 stroke risk factors using the CHA 2 DS 2 -VASc score are present [24].…”
Section: Discussionmentioning
confidence: 99%
“…This may support the need for stroke prevention in patients with AHREs which is currently under evaluation in randomized control trials; two ongoing trials are exploring this issue [19, 20]. Apart from CIEDs, increasingly sophisticated means of monitoring (e.g., implanted loop recorders) to detect AHREs in various clinical settings and high-risk groups, that would merit consideration of stroke prevention, have been recently investigated [2123]. Of note, a recent consensus document from the European Heart Rhythm Association recommended that patients presenting with subclinical atrial tachyarrhythmias (i.e., AHRE > 5 min) should be considered for oral anticoagulation when ≥ 2 stroke risk factors using the CHA 2 DS 2 -VASc score are present [24].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical practice guidelines, including those published by the Canadian Cardiovascular Society (CCS), American Heart Association (AHA), and the European Society of Cardiology (ESC), recommend that health care providers risk‐stratify patients with clinical AF to predict their risk‐benefit ratio for taking OAC . However, in many cases where AF is detected transiently while patients are hospitalized for an acute stressor (eg, medical illness or following surgery), OAC is not prescribed . AF in this setting may be due to a combination of underlying myocardial substrate and triggering pathophysiologic factors, but its detection may also be explained in some part by continuous inpatient heart rhythm monitoring …”
Section: Background and Rationalementioning
confidence: 99%
“…AFOTS is detected with variable frequency . In our previous work, we reviewed the incidence of AFOTS and the recurrence of AF following an acute medical stressor .…”
Section: Background and Rationalementioning
confidence: 99%
“…However, in some cases, AF detected after acute IS may be shortlasting and perhaps a nonrecurrent autonomic and inflammatory epiphenomena of stroke, so some patients may face an unnecessary risk of bleeding (Haeusler et al, 2018). In addition, more knowledge is needed to determine the mediating mechanism of AF detected after IS, and to effectively prevent the occurrence of new-onset AF after IS (Sposato et al 2014;Scheitz et al 2015;Fauchier et al 2017). Previous population-based observational studies found that IS has been established as a risk factor of AF (Rizos et al 2015;Luo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%